Comparing behavior between a large sample of smart students and a representative sample of Japanese adults - Nobuyuki Hanaki; Keigo Inukai; Takehito Masuda; Yuta Shimodaira (Osaka University, Institute of Social and Economic Research (ISER), 2022)
We address a concern about the external validity, in particular, the representativeness of the sampled population, of an experiment conducted with university students. We do so by conducting largescale (partly) incentivized online surveys of students at a Japanese university and of a sample of Japanese adults to measure individual characteristics such as cognitive ability, mentalizing skills, preferences for risk and distribution, and personality traits. While significant differences between these two samples are observed in many of these characteristics, the correlational structures among these characteristics are very similar in the two samples.
Keywords: C91; D91; 330; external validity; individual characteristics